Synthesis of nanoparticles in dual biodiesel and enchancement in performances and emission characteristics - Casmir Jayaseelan George Antony; Dhas Anderson Arul Ghana; Alagarsamy Senthil Kumar (Zaštita Materijala)
Biodiesel is being advertised as a realistic alternative fuel. Since it has a lower environmental effect than standard fuel properties, biodiesel has risen in popularity recently, and there has been a lot of study done on it all around the world. Biodiesel is prone to oxidation due to the presence of unsaturated fatty acids in the ester, which has been one of the biggest downsides. When biodiesel comes into contact with oxygen during storage or even with metal impurities, it oxidises. Antioxidants are really helpful in resolving problems with oxidation stability. In this paper, mainly discussed about dual biodiesel (40:60), mixed with TiO2 Nanoparticles at various 25 ppm levels for the blend DBNP20, DBNP40 and DBNP60 respectively. The results implies good performances and emission characteristics with lower SFC and reasonable values are tabulated in the with neat diesel values.